Characteristics influencing therapy switch behavior after suboptimal response to first-line treatment in patients with multiple sclerosis. (June 2014) - Teter, Barbara; Agashivala, Neetu; Kavak, Katelyn; Chouhfeh, Lynn; Hashmonay, Ron; Weinstock-Guttman, Bianca
Background: Factors driving disease-modifying therapy (DMT) switch behavior are not well understood. Objective: The objective of this paper is to identify patient characteristics and clinical events predictive of therapy switching in patients with suboptimal response to DMT. Methods: This retrospective study analyzed patients with relapsing–remitting multiple sclerosis (MS) and a suboptimal response to initial therapy with either interferon β or glatiramer acetate. Suboptimal responders were defined as patients with ≥1 MS event (clinical relapse, worsening disability, or MRI worsening) while on DMT. Switchers were defined as those who changed DMT within six to 12 months after the MS event. Results: Of 606 suboptimal responders, 214 (35.3%) switched therapy. Switchers were younger at symptom onset ( p = 0.012), MS diagnosis ( p = 0.004), DMT initiation ( p < 0.001), and first MS event ( p = 0.011) compared with nonswitchers. Compared with one relapse alone, MRI worsening alone most strongly predicted switch behavior (odds ratio 6.3; 95% CI, 3.1–12.9; p < 0.001), followed by ≥2 relapses (2.8; 95% CI, 1.1–7.3; p = 0.040), EDSS plus MRI worsening (2.5; 95% CI, 1.1–5.9; p = 0.031) and EDSS worsening alone (2.2; 95% CI, 1.2–4.1; p = 0.009). Conclusions: Younger patients with disease activity, especially MRI changes, are more likely to have their therapy switched sooner than patients who are older at the time of MS diagnosis and DMT initiation.